Atypical Presentation of Sub Acutesclerosing Pan Encephalitis With Short Onset Latency - Wardhane, S; Oswal, J; Shrivastava, K (Journal of Nepal Paediatric Society, 2015)
The most severe sequel of measles virus infection is sub acutesclerosing pan encephalitis (SSPE), a fatal disease of the central nervous system that generally develops 7–10 years after infection. A 7 ½ year old boy presented with gradual difficulty in walking and speech along with jerky movements of right upper limb which progressed to become generalized and progressive loss of cognition was also observed within days of onset of symptoms. Diagnosis of SSPE was made on the basis of burst suppression pattern on EEG and anti measles antibody in CSF. A differential diagnosis of SSPE should be considered in all forms of acute encephalopathy for early diagnosis and treatment. J Nepal Paediatr Soc 2015;35(1):62-63